2008
DOI: 10.1093/rheumatology/ken417
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin inhibits IL-1 -induced MMP-1 and MMP-3 expression in rheumatoid arthritis synovial fibroblasts

Abstract: Cordycepin is a potent inhibitor of IL-1beta-induced chemokine production and MMP expression and strongly blocks the p38/JNK/AP-1 signalling pathway in RASFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
73
1
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 43 publications
4
73
1
1
Order By: Relevance
“…Supporting our observations, cordycepin inhibits the phosphorylation of MAPK in macrophage cells (31). In our previous study, we reported that cordycepin inhibited MMP-1 and -3 expression by suppressing AP-1 activation through MAPK signaling pathway in rheumatoid arthritis synovial fibroblasts (32). Also, we have confirmed that TPA-induced MMP-9 expression was significantly inhibited by the selective inhibitor of ERK1/2 (PD98059) or JNK (SP600125) and partly inhibited by selective inhibitors of the p38 MAPK (SB203580) (data not shown), and previous studies support our data (30,33,34).…”
Section: Discussionsupporting
confidence: 87%
“…Supporting our observations, cordycepin inhibits the phosphorylation of MAPK in macrophage cells (31). In our previous study, we reported that cordycepin inhibited MMP-1 and -3 expression by suppressing AP-1 activation through MAPK signaling pathway in rheumatoid arthritis synovial fibroblasts (32). Also, we have confirmed that TPA-induced MMP-9 expression was significantly inhibited by the selective inhibitor of ERK1/2 (PD98059) or JNK (SP600125) and partly inhibited by selective inhibitors of the p38 MAPK (SB203580) (data not shown), and previous studies support our data (30,33,34).…”
Section: Discussionsupporting
confidence: 87%
“…These fungi are highly prized in Tibetan and Chinese traditional medicine and used for a large number of afflictions, including kidney, heart, and lung conditions such as asthma (Winkler 2010). A variety of studies indicate that cordycepin has clear biological activities, it is antiproliferative, antimetastatic, and anti-inflammatory, and it inhibits the unfolded protein response (Nakamura et al 2005;Lee et al 2009Lee et al , 2010Noh et al 2009;Wong et al 2010;Cheng et al 2011;Kim et al 2011;Kitamura et al 2011). Because of its structure, cordycepin could potentially interfere with any process requiring adenosine or ATP.…”
Section: Introductionmentioning
confidence: 99%
“…As individual response to drugs can vary, and as potential side effects remain one of the problems for long-term use of NSAIDs, phytochemicals are potential candidates as a novel agent to prevent inflammation for the treatment of many diseases, including OA [26]. Cordycepin, a nucleoside derivative isolated from Cordyceps, is reported to exert inhibitory effects on macrophages and RA synovial fibroblasts due to its antiinflammatory effect [12,16]. In this study, we evaluated the role of cordycepin in inflammatory responses in human articular chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Cordycepin has also been studied for antitumor [13], antidiabetic [14], and renoprotective effects [15]. Noh et al [16] demonstrated that cordycepin has anti-rheumatic and antiinflammatory effects on IL1β-stimulated rheumatoid arthritis synovial fibroblasts (RASFs). Shin et al [17] discovered that cordycepin could suppress expression of diabetes-regulating genes by inhibiting lipopolysaccharide-induced inflammation in macrophages.…”
Section: Introductionmentioning
confidence: 99%